Kansalaisuuskäsitykset ja asevelvollisuus Suomessa - Puustinen, Alisa; Kosonen, Jarkko; Tallberg, Teemu (Tiede ja ase, 2019)
Citizenship and Conscription in Finland. This article studies relationships between citizens, state and national defence in Finland. Conscription and different perceptions of citizenship form the framework where civic rights and duties were examined. Data was collected in individual and group interviews of 71 interviewees and analysed by using content-driven content analysis. International literature suggests that there are two major drivers that can be connected to changing perceptions of citizens’ rights and duties: individualization and globalization (cosmopolitanism). These have often been articulated with the erosion of both citizenship and willingness to serve in armed forces. Our empirical analysis suggests that the most prominent of these drivers is individualization. Individualization in the form of optimizing personal benefits and choice is the most common explanatory factor when choosing the civil service over military service, or behind the decision to resign from the reserve forces. Reasons related to ethical conviction, globalization or cosmopolitanism is in the margins. It can be concluded that the welfare state citizenship, as we conceptualized it, is prevailing in Finland. The state presents citizens with social, political and individual civic rights without actual claims of reciprocity of the fulfilment of civic duties.